The effectiveness of a stage-based lifestyle modification intervention for obese children - Md. Yusop, Nor Baizura; Mohd Shariff, Zalilah; Hwu, Ting Tzer; Abd. Talib, Ruzita; Spurrier, Nicola (BioMed, 2018)
Background: Interventions that encompass behavioural modifications of dietary intake and physical activity are essential for the management of obesity in children. This study assessed the effectiveness of a stage-based lifestyle modification intervention for obese children. Methods: A total of 50 obese children (7–11 years old) were randomized to the intervention group (IG, n = 25) or the control group (CG, n = 25). Data were collected at baseline, at follow-up (every month) and at six months after the end of the intervention. IG received stage-based lifestyle modification intervention based on the Nutrition Practice Guideline for the Management of Childhood Obesity, while CG received standard treatment. Changes in body composition, physical activity and dietary intake were examined in both the intervention and control groups. Results: Both groups had significant increases in weight (IG: 1.5 ± 0.5 kg; CG: 3.9 ± 0.6 kg) (p < 0.01) and waist circumference (IG: 0.1 ± 0.5 cm; CG: 2.2 ± 0.7 cm) (p < 0.05), but the increases were significantly higher in CG than IG. Body Mass Index (BMI)-for-age z scores decreased significantly in IG (− 0.2 ± 0.0, p < 0.01) but not in CG. The physical activity of the IG significantly increased (0.44 ± 0.13) compared with that of CG (− 0.28 ± 0.18), and the difference in mean change between groups was statistically significant (p < 0.05). Dietary intake was not significantly different between the two groups. However, calorie and carbohydrate intake decreased significantly in both groups. Conclusions: A stage-based intervention that modified dietary and physical activity behaviour may be effective in weight management for obese children.